Neuromagnetic representation of musical register information in human auditory cortex - Andermann, Martin; van Dinther, Ralph; Patterson, Roy D.; Rupp, André (NeuroImage, 2011)
Pulse-resonance sounds like vowels or instrumental tones contain acoustic information about the physical size of the sound source (pulse rate) and body resonators (resonance scale). Previous research has revealed correlates of these variables in humans using functional neuroimaging. Here, we report two experiments that use magnetoencephalography to study the neuromagnetic representations of pulse rate and resonance scale in human auditory cortex. In Experiment 1, auditory evoked fields were recorded from nineteen subjects presented with French horn tones, the pulse rate and resonance scale of which had been manipulated independently using a mucoder. In Experiment 2, fifteen subjects listened to French horn tones which differed in resonance scale but which lacked pulse rate cues. The resulting cortical activity was evaluated by spatio-temporal source analysis. Changes in pulse rate elicited a well-defined N1m component with cortical generators located at the border between Heschl's gyrus and planum temporale. Changes in resonance scale elicited a second, independent, N1m component located in planum temporale. Our results demonstrate that resonance scale can be distinguished in its neuromagnetic representation from cortical activity related to the sound's pulse rate. Moreover, the existence of two separate components in the N1m sensitive to register information highlights the importance of this time window for the processing of frequency information in human auditory cortex.